O cinema como instrumento didático para a abordagem de problemas bioéticos: uma reflexão sobre a eutanásia - Dantas, Anielle Avelina (2008)
Advances in medical knowledge and constant technological innovations which have provided tools for the practice of medicine have relevant repercussions in the ethical and social fields. These give significance and pertinence to a permanent multidisciplinary look at the intrinsic relationship between medical science and the humanities Indeed, medicine and health are a human concern in the fullest sense. Bodies, minds, emotions and human relations are explored and expressed both by arts and humanities and by science. Medical students share people s significant, sometimes dramatic moments: births, deaths, physical handicaps, suffering and life-threatening diseases. The approach to arts and humanities may make it possible to obtain truly critical, human and ethical answers to these difficulties, since they deal with reflexive questions about the memory and interpretation of human experience. The humanities explore the ambiguity, uncertainty and complexity of human life carefully, with theoretical lucidity. Since they deal with issues involving human subjectivity in a critical and logical form, they offer the elements for reasoning by means of synthesis and analysis, which are needed for the practice of medicine. From the perspective of education, medical humanities may also help in the development of the capacity for critical conceptualization and analysis of professional or personal values, besides promoting reflection on the interpersonal relations of empathy, and team work. In this sense, arts and human sciences may have something to contribute to the conceptual repositioning of medicine itself. The study of humanities may not be able to make physicians more human, but it can create greater understanding and knowledge about the human experience. Teaching ethics, and particularly moral judgment, is necessary and essential to educate medical students, since caring for the health of individuals and populations presupposes actions and decisions that must be permanently evaluated rationally, with regard to their real, effective repercussions. The art of film can stimulate a critical evaluation and the real understanding of the patients narratives and unique needs. The purpose of this study is to show that the structured analysis of a commercial film can be an instructive activity which facilitates achieving the educational aims involving the teaching of bioethics, and in particular, the moral problems concerning euthanasia. By means of a macro and microanalytic interpretation of the commercial film, Mar Adentro (The Sea Inside, 2004), examples were identified of teaching-learning situations and opportunities. A few summary descriptions were made of a few scenes, and in them the different ways the characters saw the scene were highlighted. The criterion used to choose the scenes was based on their capacity to reveal contents and situations that could stimulate reflection about the moral/bioethical dilemmas of the right to life. Having the students watch a complete commercial film, followed by the discussion of scenes can be used as a significant pedagogical instrument to attain the humanistic educational aims of the Medical courses.